A study of black matric pupils who make traditional career choices versus non-traditional career choices with regard to personality traits, vocational needs and family background - Maesela, Jennifer Pinkie (Stellenbosch : Stellenbosch University, 2012)
Thesis (M.A.) -- University of Stellenbosch, 1994.